2008
DOI: 10.1128/mcb.01119-07
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha Catalytic Subunit of Protein Kinase CK2 Is Required for Mouse Embryonic Development

Abstract: Protein kinase CK2 (formerly casein kinase II) is a highly conserved and ubiquitous serine/threonine kinase that is composed of two catalytic subunits (CK2␣ and/or CK2␣) and two CK2␤ regulatory subunits. CK2 has many substrates in cells, and key roles in yeast cell physiology have been uncovered by introducing subunit mutations. Gene-targeting experiments have demonstrated that in mice, the CK2␤ gene is required for early embryonic development, while the CK2␣ subunit appears to be essential only for normal spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
175
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(189 citation statements)
references
References 54 publications
8
175
1
2
Order By: Relevance
“…Experiments in yeast and mice have shown that CK2a and CK2b are essential for viability. CK2a' knockout mice are viable but male mice are sterile [3][4][5][6][7][8]. This observation suggests a functional specialization between CK2a and CK2a' where CK2a can at least partially compensate for the loss of CK2a'.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Experiments in yeast and mice have shown that CK2a and CK2b are essential for viability. CK2a' knockout mice are viable but male mice are sterile [3][4][5][6][7][8]. This observation suggests a functional specialization between CK2a and CK2a' where CK2a can at least partially compensate for the loss of CK2a'.…”
mentioning
confidence: 76%
“…There is some indication that CK2 plays a role in spermatogenesis [8,7,23] as well as during certain stages of embryogenesis [24,25]. Furthermore, it was shown by several groups that CK2 seems to be an important protein kinase for a variety of different cellular processes in developing organs and organogenesis [5,6,26,27]. In the differentiation of pre-adipocytes into adipocytes, CK2 was found to be accompanied by a decrease in the protein level and in the kinase activity [28,29].…”
mentioning
confidence: 99%
“…Mice lacking the more abundant, major CK2α subunit die at mid-gestation (E9.5-E10.5) due to neural tube defects, improper branchial arch and heart development. The latest one is likely the causative of the mid-gestational lethality [320]. Multiple studies indicate the importance of normal CK2 function is the specification of muscle, neuronal, adipose, osteogenic, hematopoietic, or germ lineage differentiation and stem cells self-renewal process.…”
Section: Ncprc13 and Ncprc15mentioning
confidence: 99%
“…The catalytic CK2 subunits share a high degree of homology except for the C-terminal part (5) and not much is known about the functional difference between the two catalytic subunits. Their functions appear redundant, however mice deficient in CK2α die during early embryogenesis (6), whereas mice deficient in CK2α' appear normal, although the male mice are sterile due to abnormal spermatogenesis (4), suggesting that the two catalytic subunits have functions which can not be substituted by the other.…”
Section: Introductionmentioning
confidence: 99%